The Economics of Sexed Semen in Dairy Heifers and Cows - Albert De Vries (EDIS)
AN214, a 13-page fact sheet by Albert De Vries, summarizes the recent literature on sexed semen use in dairy heifers and cows and evaluates the economics of the use of sexed semen in heifers and cows. Includes references. Published by the UF Department of Animal Sciences, March 2009.